Severe and fatal adverse events of immune checkpoint inhibitor combination therapy in patients with metastatic renal cell carcinoma: a systematic review and meta-analysis - Yao-Ning Feng; Guang-Yu Xie; Li Xiao; Dun-Chang Mo; Jian-Feng Huang; Peng-Hui Luo; Xiu-Juan Liang (Frontiers in Immunology, 2023)
IntroductionImmune checkpoint inhibitor (ICI) combination therapy has changed the treatment landscape for metastatic renal cell carcinoma (mRCC). However, little evidence exists on the treatment-related severe adverse events (SAEs) and fatal adverse events (FAEs) of ICI combination therapy in mRCC.MethodWe searched PubMed, Embase, and Cochrane Library databases to evaluate randomized controlled trials (RCTs) of ICI combination therapy versus conventional tyrosine kinase inhibitor (TKI)-targeted therapy in mRCC. Data on SAEs and FAEs were analyzed using revman5.4 software.ResultsEight RCTs (n=5380) were identified. The analysis showed no differences in SAEs (60.5% vs. 64.5%) and FAEs (1.2% vs. 0.8%) between the ICI and TKI groups (odds ratio [OR], 0.83; 95%CI 0.58−1.19, p=0.300 and OR, 1.54; 95%CI 0.89−2.69, p=0.120, respectively). ICI-combination therapy was associated with less risk of hematotoxicities, including anemia (OR, 0.24, 95%CI 0.15–0.38, p<0.001), neutropenia (OR, 0.07, 95%CI 0.03–0.14, p<0.001), and thrombocytopenia (OR, 0.05, 95%CI 0.02−0.12, p<0.001), but with increased risks of hepatotoxicities (ALT increase [OR, 3.39, 95%CI 2.39–4.81, p<0.001] and AST increase [OR, 2.71, 95%CI 1.81−4.07, p<0.001]), gastrointestinal toxicities (amylase level increase [OR, 2.32, 95%CI 1.33–4.05, p=0.003] and decreased appetite [OR, 1.77, 95%CI 1.08–2.92, p=0.020]), endocrine toxicity (adrenal insufficiency [OR, 11.27, 95%CI 1.55–81.87, p=0.020]) and nephrotoxicity of proteinuria (OR, 2.21, 95%CI 1.06−4.61, p=0.030).ConclusionsCompared with TKI, ICI combination therapy has less hematotoxicity in mRCC but more specific hepatotoxicity, gastrointestinal toxicity, endocrine toxicity, and nephrotoxicity, with a similar severe toxicity profile.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023412669.